Pengembangan tes ilmu pengetahuan alam terkomputerisasi - Suwarto, Suwarto (Jurnal Penelitian dan Evaluasi Pendidikan, 2017)
Penelitian ini bertujuan untuk: (1). Memaparkan karakteristik tes IPA yang dikembangkan, dan (2) memaparkan program komputer yang telah dikembangkan dalam menentukan skor tes siswa dengan teori tes modern. Tes IPA terdiri dari 600 butir soal dan telah diujicobakan di SMP se-Solo Raya dengan responden 1.800 siswa. Teknik analisis data yang digunakan adalah program R. Program komputer yang telah dikembangkan diujicobakan di SMP Negeri 4 Polokarto. Hasil analisis tes IPA dengan program R menunjukan: (1) tingkat kesulitan butir dalam kisaran -2,001 sampai 1,713, (2) daya beda butir dalam kisaran 0,553 sampai 2,394, dan (3) terkaan butir dalam kisaran 0,000 sampai 0,379. Program komputer yang dikembangkan dapat menentukan skor tes siswa menurut teori tes modern dengan baik. DEVELOPING OF COMPUTERIZED NATURAL SCIENCE TESTAbstractThis study is aimed at: (1) describing the caracteristics of Natural Science test developed, and (2) describing a computer program which had been developed to determine the test scores of students with modern test theory. Natural Science test consists of 600 items and had been tested in junior high school throughout Solo Raya with 1,800 respondents. Data analysis technique which was used is R programming. The computer program had been developed and tested in SMP Negeri 4 Polokarto (Polokarto 4 Junior High School). The results of the analysis of Natural Science program test with R programming show that: (1) item difficulty is in the range of -2.001-1.713, (2) discriminatory power of items is in the range of 0.553-2.394, and (3) the supposition of items is in the range of 0.000-0.379. The computer program developed can determine students’ test scores according to the modern test theory well.